Apoptosis repressor with caspase recruitment domain deficiency accelerates ischemia/reperfusion (I/R)-induced acute kidney injury by suppressing inflammation and apoptosis: The role of AKT/mTOR signaling - Ke Yingjie (Biomedicine & Pharmacotherapy, 2019)
Acute kidney injury (AKI) is a significant medical problem worldwide. Ischemia-reperfusion (I/R) injury of the kidney is a major cause of AKI. However, the pathogenesis that contributes to renal I/R injury is still unclear. Apoptosis repressor with caspase recruitment domain (ARC) is abundantly expressed in various tissues, and has been reported to play a strong protective role during pathological processes. Our results indicated that ARC expression was decreased in the reperfused kidneys. ARC deficiency markedly accelerated renal dysfunction, promoted reperfusion-regulated tubular epithelial cell apoptosis, and enhanced the vulnerability of kidney to I/R damage. Furthermore, in the kidney samples of mice underwent renal I/R injury, ARC knockout significantly accelerated the expression levels of inflammatory factors, including interleukin (IL)-1β, IL-6, tumor necrosis factor a (TNF-α), monocyte chemoattractant protein-1 (MCP-1) and IL-2. In addition, renal I/R injury-induced apoptosis was further exacerbated in ARC-deficient mice through promoting the expression of cleaved Caspase-3 and poly (ADP-ribose) polymerase (PARP). From the molecular level, ARC deletion obviously accelerated mitochondrial injury, as evidenced by the further decreased adenosine triphosphate (ATP) levels and mitochondrial potential in hypoxia-reoxygenation (H/R)-treated cells. Moreover, ARC knockout exacerbated AKI through activating phosphorylated protein kinase B (AKT), mammalian target of Rapamycin (mTOR) and p53, whereas reducing phosphorylated glycogen synthase kinase 3β (GSK3β). Of note, blocking AKT/mTOR signaling markedly attenuated inflammation, mitochondrial damage and apoptosis stimulated by H/R in ARC knockdown cells. In summary, our results suggested that ARC played a pivotal role in the pathogenesis of AKI induced by renal I/R operation through regulating AKT/mTOR signaling.